The use of renewable resources is an opportunity and an obligation - Balla, Zoltán (Acta Agraria Debreceniensis, 2014)
The renewable energy sources could be used in energy production, while no or only very slightly emit harmful substances to the environment. The solar, wind, hydropower, biomass and heat rational utilization of land contributes to greenhouse gas emissions. Renewable energy sources also reduces the dependence on fossil fuels, thus contributing to increase security of supply. The creation of local jobs to strengthen the area’s population retaining ability.